Annealing effect on the electrical proprieties of IF(CN2)2-meta based OTFTs: Thermal behavior and modeling of charge transport. (November 2018) - Arfaoui, N.; Mahdouani, M.; Bouhadda, I.; Poriel, C.; Bourguiga, R.; Jacques, E.; Chevrier, M.; Bebiche, S.
Abstract: N-type organic thin film transistors (OTFT) based on IF(CN2 )2 -meta were fabricated in bottom gate-bottom contact configuration at substrate temperature of 80 °C and deposition rate dr of 0, 4 Å/s, using the epoxy based photoresist SU-8 as gate insulator. A thermal annealing of fabricated devices under nitrogen for 90 min at 150 °C has enhanced their performances. In order to understand the annealing effect on the performance of IF(CN2 )2 -meta based OFETs, we have analyzed their thermal behavior by characterizing them electrically over a temperature range from 300 up to 380 K while 10 K step was used. Accordingly, we have estimated and compared the activation energy of the mobility Ea and the density of state DOS before and after annealing treatment. The present study has shown that the improvement of OFETs performances is due to the increased crystallinity of IF(CN2 )2 -meta layer thereby to the enhanced SU-8/IF(CN2 )2 -meta and Au/IF(CN2 )2 -meta interfaces. Finally, to understand the charge transport mechanism dominating in the IF(CN2 )2 -meta molecule and to model the fabricated OFETs, we have successfully reproduced the dependence of mobility with temperature and the transfer and output characteristics using an analytical model based on variable range hopping (VRH) theory. Graphical abstract: Highlights: IF(CN2 )2 -meta based TFTs were fabricated with SU-8 as organic gate insulator. The performances of fabricated devices were enhanced by thermal annealing. The annealing effect on the activation energy and the DOS was investigated. VRH model was successfully applied to the IF(CN2 )2 -meta based OFETs. The model results are in good agreement with the experimental data.